2014
DOI: 10.1373/clinchem.2014.222430
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Troponin I Associated with the Development of Unrecognized Myocardial Infarctions Detected with MRI

Abstract: BACKGROUND:Late enhancement MRI (LE-MRI) and cardiac troponin I (cTnI) are sensitive methods to detect subclinical myocardial injury. We sought to investigate the relation between plasma concentrations of cTnI measured with a high-sensitivity assay (hs-cTnI) and the development of unrecognized myocardial infarctions (UMIs) detected with LE-MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The acquired slice thickness was 10 mm with a resolution of 1.56 x 2.81 mm and the inversion time was individually adjusted. Cine images were acquired during breath holding using asteady state free precession sequence as previously described [ 2 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…The acquired slice thickness was 10 mm with a resolution of 1.56 x 2.81 mm and the inversion time was individually adjusted. Cine images were acquired during breath holding using asteady state free precession sequence as previously described [ 2 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…The level of serum cTn-I was increased in three to five hours, followed by continuous disruption and destruction of myofibril, and cTn-I was constantly released, therefore, cTn-I is a serum marker of high sensitivity and specificity for reflection of myocardial cell damage. 7 A previous study showed both serum cTn-I and CK-MB were significantly increased on the first day of neonatal asphyxia, showing a positive correlation. 8 Therefore, the indicators are of great significance to the diagnosis of myocardial damage and judgment of efficacy and prognosis.…”
Section: Discussionmentioning
confidence: 90%
“…19 In addition, post-PCI cardiac troponin is of little value as a prognostic factor compared to pre-PCI level. 12,20 On the other hand, chronic elevation of high-sensitivity cardiac troponin level was associated with chronic myocardial injury in the asymptomatic population 21 and was an independent predictor of composite major cardiac adverse events in diabetic patients with SCAD. 9 Furthermore, although a strong association between hs-cTnT and coronary artery plaque burden, or inducible cardiac ischemia, in patients with SCAD has been identified, 3-5 prompt revascularization did not affect the concentration of hs-cTnT at follow-up or clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%